Saberes e fazeres etnomatemáticos na agricultura guarani - Morais, Marcia Dahmer de (2024)
This research has as its main objective to provide traditional knowledge and practices present in Guarani family farming, particularly concerning to its mathematics, emphasizing those that are used by indigenous people on a daily basis, strengthening the historical knowledge and struggles of these unique groups. The research was performed in the Guarani Tekoha Ocoy indigenous community, located in the municipality of São Miguel do Iguaçu-PR, with a Guarani family whose traditions are directly linked to the routine of the majority of students at the Teko Ñemoingo Indigenous State School, an educational institution in the community where the researcher works as a teacher. In methodological terms, through participant observation, investigative actions were carried out, relating cultural knowledge linked to indigenous agriculture, especially their own and local knowledge and practices, considering the importance of this study for contextualized cultural practices and highlighting that mathematics is not only learned in the classroom, but in all social spaces. For this, the line of the Ethnomathematics Program was used, which defends a closer relationship between school knowledge and practices with that of the daily practice of the Guarani and their knowledge and worldview, such as, for example, about planting and harvest cycles as well as Nhemongarai which is very important for these people to have the seeds consecrated, and then, plant, thanking and asking for protection until harvest time arrives. Finally, strengthening the research's commitment to identifying traditional ethnomathematical knowledge and practices used by the Guarani indigenous people in their family agriculture, highlighting some parallels with the worldview, culture and spirituality of this indigenous community, while they take care of their kokue (field).